Successful control of major project budgets - Steen Lichtenberg (Administrative Sciences, 2016)
This paper differs from scientific papers describing current research. In line with the theme of this special issue, it challenges conventional risk management practice against the background of former research results successfully finished decades ago. It is well-known that conventional practice frequently results in budget overruns of large projects. International reviews document that. Severe delays of schedules are also well-known. This paper describes successful research results from almost three decades ago, which successfully challenges this severe problem and has led to new practices. The research involved is an unusual mix: Scandinavian researchers from psychology, statistical theory and engineering economy. The resulting procedure has been widely used since around 1990 and challenges conventional procedures. The procedure is documented to be able to yield statistically correct prognoses, when the "rules of the game" have been correctly followed. After a short summary of the basic situation, this paper summarizes the research, followed by some resulting experiences, focusing on two recent studies each of 40 infrastructures and other major projects. In both sets, the actual final cost largely equaled the expected project cost. This result is a marked change from international past and present experience. Finally, the need for further research and progress is discussed.
Keywords: 350; budget quality assurance; cost estimation; estimation methodology; major projects; risk management; scheduling; Successive Principle